Educação escolar quilombola : uma perspectiva identitária a partir da Escola Estadual Maria de Arruda Muller. - Ferreira, Augusta Eulália (2015)
This study is the result of an ethnographic research conducted at the Abolition community, located in a quilombola territory, in the municipality of Santo Antônio de Leverger, in the Mato Grosso state. It aims to describe the meaning of the Quilombola Schooling as specific and differentiated in this territory and the relationships established between the local and traditional knowledges developed in the State School Maria de Arruda Muller, located within this community. For this purpose, I analyze the role of this school in strengthening the social organization of the community, in the participation of the individuals in the political processes, in the affirmation of an identity and of the feeling of belonging to the quilombola territory and in the struggles for social rights as a group. The central contribution that I choose were the concepts of Geertz (2012) on Ethnography, whose interpretations and analyzes presented in this study are based on the speeches, observations and interviews expressed by managers, teachers, students and residents of the community Abolition. An effort was made to make them important theoretical elements for the studies in favor of an education for ethnic-raciais relations in the quilombola territory. This research reveals part of the conflict that permeates the community. This conflict constitutes an important factor for understanding the dynamics of an identity being gestated and experienced in the School Maria de Arruda Muller. The results reveal some obstacles in the actualization of the quilombola school education proposal. These obstacles are revealed from the relationship between the quilombolas with the school, of its role as a mediator of the formation or of the strengthening of quilombola identity and of the ethnic-raciais relations in the wide sense. These obstacles are directly linked to the reproduction of an colonialistic and eurocentric education that still nowadays marking the education, in general, and also this quilombola school. This reproduction is materialized in the limitations to implement a school which, even ensuring the physical structure, does not guarantee an education in line with the history and territoriality of the community.